Effects of pioglitazone on cardiac and adipose tissue pathology in rats with metabolic syndrome. (20th January 2015) - Matsuura, Natsumi; Asano, Chiharu; Nagasawa, Kai; Ito, Shogo; Sano, Yusuke; Minagawa, Yuji; Yamada, Yuichiro; Hattori, Takuya; Watanabe, Shogo; Murohara, Toyoaki; Nagata, Kohzo
Abstract: Background: Pioglitazone is a thiazolidinedione drug that acts as an insulin sensitizer. We recently characterized DahlS.Z- Lepr fa / Lepr fa (DS/obese) rats, derived from a cross between Dahl salt-sensitive and Zucker rats, as a new animal model of metabolic syndrome. We have now investigated the effects of pioglitazone on cardiac and adipose tissue pathology in this model. Methods and results: DS/obese rats were treated with pioglitazone (2.5 mg/kg per day, per os) from 9 to 13 weeks of age. Age-matched homozygous lean (DahlS.Z- Lepr + / Lepr +, or DS/lean) littermates served as controls. Pioglitazone increased body weight and food intake in DS/obese rats. It also ameliorated left ventricular (LV) hypertrophy, fibrosis, and diastolic dysfunction as well as attenuated cardiac oxidative stress and inflammation, without lowering blood pressure, in DS/obese rats, but it had no effect on these parameters in DS/lean rats. In addition, pioglitazone increased visceral and subcutaneous fat mass but alleviated adipocyte hypertrophy and inflammation in visceral adipose tissue in DS/obese rats. Furthermore, pioglitazone increased the serum concentration of adiponectin, induced activation of AMP-activated protein kinase (AMPK) in the heart, as well as ameliorated glucose intolerance and insulin resistance in DS/obese rats. Conclusions: Treatment of DS/obese rats with pioglitazone exacerbated obesity but attenuated LV hypertrophy, fibrosis, and diastolic dysfunction, with these latter effects being associated with the activation of cardiac AMPK signaling likely as a result of the stimulation of adiponectin secretion. Highlights: We investigate the effects of pioglitazone on cardiac and adipose tissue pathology in rats with metabolic syndrome. Pioglitazone increases body weight and food intake. Pioglitazone ameliorates cardiac injury as well as attenuates cardiac oxidative stress and inflammation. Pioglitazone alleviates adipocyte hypertrophy and inflammation in visceral adipose tissue. Pioglitazone activates cardiac AMPK signaling likely as a result of the stimulation of adiponectin secretion.